Role of surface wind and vegetation cover in multi-decadal variations of dust emission in the Sahara and Sahel. (January 2017) - Kim, Dongchul; Chin, Mian; Remer, Lorraine A.; Diehl, Thomas; Bian, Huisheng; Yu, Hongbin; Brown, Molly E.; Stockwell, William R.
Abstract: North Africa, the world's largest dust source, is non-uniform, consisting of a permanently arid region (Sahara), a semi-arid region (Sahel), and a relatively moist vegetated region (Savanna), each with very different rainfall patterns and surface conditions. This study aims to better understand the controlling factors that determine the variation of dust emission in North Africa over a 27-year period from 1982 to 2008, using observational data and model simulations. The results show that the model-derived Saharan dust emission is only correlated with the 10-m winds (W10m) obtained from reanalysis data, but the model-derived Sahel dust emission is correlated with both W10m and the Normalized Difference Vegetation Index (NDVI) that is obtained from satellite. While the Saharan dust accounts for 82% of the continental North Africa dust emission (1340–1570 Tg year −1 ) in the 27-year average, the Sahel accounts for 17% with a larger seasonal and inter-annual variation (230–380 Tg year −1 ), contributing about a quarter of the transatlantic dust transported to the northern part of South America. The decreasing dust emission trend over the 27-year period is highly correlated with W10m over the Sahara (R = 0.92). Over the Sahel, the dust emission is correlated with W10m (R = 0.69) but is also anti-correlated with the trend of NDVI (R = -0.65). W10m is decreasing over both the Sahara and the Sahel between 1982 and 2008, and the trends are correlated (R = 0.53), suggesting that Saharan/Sahelian surface winds are a coupled system, driving the inter-annual variation of dust emission. Highlights: Vegetation modulates bareness over Sahel and is anti-correlated with emission. Surface wind drives the inter-annual variation of Saharan/Sahelian dust emission. The Sahara and Sahel account for 82% and 17% of North Africa dust emission.